A porous carbon material for silicon-carbon negative electrodes and a preparation method thereof
By designing a porous carbon material with a hierarchical pore structure and a conductive reinforced shell, the problems of insufficient cycle stability and electrical performance of silicon-carbon composite materials in the prior art have been solved, and the performance of lithium-ion batteries has been improved.
Patent Information
- Application Number
- CN202511370684.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-24
- Publication Date
- 2026-02-10
- Estimated Expiration
- 2045-09-24
AI Technical Summary
Existing technologies cannot simultaneously achieve high porosity, high conductivity, strong expansion suppression, and environmentally friendly processes, resulting in insufficient cycle stability and electrical performance of silicon-carbon composite materials in lithium-ion batteries.
A porous carbon framework with a hierarchical pore structure is designed, combined with silicon-based active units and a conductive reinforced shell, and formed into a porous carbon material through specific process steps such as high-speed shear emulsification, gas-phase pyrolysis and nitrogen doping.
This approach achieves effective buffering of silicon-based active units and construction of conductive networks, improving the cycle stability and electrochemical performance of lithium-ion batteries while avoiding electrode structure damage and interfacial contact resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of lithium-ion battery anode materials, specifically relating to a porous carbon material for silicon-carbon anodes and its preparation method. Background Technology
[0002] Lithium-ion batteries play a crucial role in modern electronics, electric vehicles, and large-scale energy storage systems. One of the key factors in improving battery energy density is the development of high-performance anode materials. Silicon, with its extremely high theoretical specific capacity of approximately 4200 mAh / g, is considered an ideal candidate for next-generation anode materials. However, silicon undergoes significant volume changes during lithium-ion insertion and extraction, with volume expansion rates reaching 300% or even higher. This massive volume effect leads to electrode particle breakage, loss of electrical contact between the active material and the conductive network, ultimately resulting in electrode pulverization and rapid capacity decay.
[0003] To address the volume expansion problem of silicon, the current mainstream technical approach is to composite silicon with carbon materials. Carbon's excellent electrical conductivity and certain mechanical buffering capabilities are used to alleviate stress and improve cycle stability. Porous carbon materials, due to their tunable pore structure, high specific surface area, and good electrical conductivity, are often used as matrices or coatings to accommodate silicon particles. An ideal pore structure should be able to accommodate the expansion of silicon particles while ensuring rapid ion and electron transport. Several methods have been explored for preparing silicon-carbon composites, such as using organic precursors like phenolic resins to carbonize the surface of silicon particles to form a carbon coating, or using template methods to prepare porous carbon with specific pore structures before compositing it with silicon.
[0004] However, existing technologies have several significant drawbacks. First, during carbonization, the carbon layer is prone to shrinkage and densification, resulting in less than ideal porosity and pore size distribution. In particular, the micropores and mesopores required for ion diffusion are easily blocked, with porosity typically below 20%, limiting the effective utilization of silicon capacity. Second, to create an effective pore structure, many methods rely on strong acid or strong base etching processes, such as using hydrofluoric acid to remove hard templates (e.g., silica spheres). These processes not only cause severe equipment corrosion but also generate large amounts of highly toxic fluorine- or chlorine-containing waste liquids, leading to high treatment costs and environmental pollution. Third, controlling the dispersion of silicon particles in porous carbon matrices is a challenge. Silicon particles tend to agglomerate, leading to localized expansion stress concentration, which even a carbon layer cannot effectively suppress.
[0005] Furthermore, nitrogen doping and other techniques have been introduced to improve the conductivity of carbon materials. However, these doping processes often require the introduction of reducing gases such as ammonia at high temperatures, resulting in complex processes, significantly increased costs, and safety risks. Existing technologies have failed to simultaneously achieve the key elements of high porosity, high conductivity, strong expansion suppression, and environmentally friendly processes.
[0006] Therefore, it is necessary to design a porous carbon material for silicon-carbon anodes and a preparation method thereof. Summary of the Invention
[0007] To overcome the shortcomings of the prior art, a porous carbon material for silicon-carbon anodes and its preparation method are provided.
[0008] To achieve the above objectives, the present invention provides the following technical solution:
[0009] A porous carbon material for silicon-carbon anodes, the porous carbon material for silicon-carbon anodes having the following structure:
[0010] Porous carbon framework: It has a hierarchical pore structure, including micropores with a pore size of 0.5-2 nm, mesopores with a pore size of 10-30 nm, and macropores with a pore size of 100-300 nm.
[0011] Silicon-based active units: uniformly dispersed in the mesopores and macropores of the porous carbon framework, wherein the silicon-based active units are composed of a nano-silicon particle core and a silicon suboxide layer covering its surface;
[0012] Conductive reinforced shell: a vapor-phase pyrolysis carbon layer that completely covers the outer surface of the composite material consisting of a porous carbon framework and silicon-based active units.
[0013] The porous carbon framework has a porosity of 38-45%, of which micropores account for 40-60%, mesopores account for 25-40%, and the remainder is macropores.
[0014] The thickness of the conductive reinforced shell is 2-8 nanometers.
[0015] The silicon-based active unit accounts for 25-40% of the total mass of the porous carbon material used in the silicon-carbon anode. The average particle size of the nano-silicon particle core in the silicon-based active unit is 80-150 nanometers, and the thickness of the silicon suboxide layer is 5-15 nanometers with an oxygen-silicon atomic ratio of 0.8-1.2.
[0016] The inner surface of the hierarchical pore structure of the porous carbon skeleton is modified with carboxyl groups, which form chemical bonds with the silicon suboxide layer of the silicon-based active unit.
[0017] A method for preparing a porous carbon-based material for silicon-carbon anodes, the method comprising the following steps:
[0018] Step A: Preparation of porous carbon framework precursor: Lignocellulose is heated in an argon atmosphere tube furnace to obtain pre-carbonized products;
[0019] Step B: Graded pore-forming treatment: Immerse the pre-carbonized product in a mixed activator solution, control the solid-liquid mass ratio to 1:5 to 1:8, and stir continuously at 80-95℃ for 180 minutes to obtain a primary porous carbon skeleton.
[0020] Step C: Surface functionalization treatment: Immerse the primary porous carbon skeleton in a surface modifier, remove it after 30 minutes, and dry and cure it to obtain a surface-modified carbon skeleton with a silane coupling layer formed on its surface.
[0021] Step D: Silicon-based active unit composite: The surface-modified carbon skeleton is subjected to high-speed shear emulsification, while silicon-based active unit raw materials are added in batches, and atomized coal tar pitch is sprayed in to obtain a pre-composite.
[0022] Step E: Construction of conductive reinforced shell: The precomposite is transferred into a fluidized bed reactor and a mixed gas of acetylene and argon in a volume ratio of 1:4-5 is introduced. The mixture is then pyrolyzed and deposited at 650-750℃ for 45-60 minutes to form a carbon-coated silicon-carbon composite with a gas-phase pyrolyzed carbon layer on the surface.
[0023] Step F: Elemental doping treatment: Using carbon-coated silicon-carbon composite as raw material, elemental doping is performed in a mixed atmosphere to obtain nitrogen-doped silicon-carbon composite;
[0024] Step G: Channel Functionalization: The inner surface of the nitrogen-doped silicon-carbon composite is modified to modify the hierarchical pore structure with carboxyl groups, resulting in the finished porous carbon material for silicon-carbon anodes.
[0025] In step A, the specific parameters are as follows: 100-200 mesh lignocellulose is placed in an argon atmosphere tube furnace and heated to 450-550°C at a rate of 10°C per minute, and held for 60 minutes to obtain a pre-carbonized product.
[0026] In step B, the mixed activator solution comprises: 15-25 parts by mass of potassium hydroxide, 8-15 parts by mass of diammonium hydrogen phosphate, and 60-80 parts by mass of deionized water.
[0027] In step C, the surface modifier is an ethanol solution of silane coupling agent KH-550 with a mass percentage concentration of 2.5%-3.5%; the drying and curing are carried out under vacuum conditions of 0.02-0.04 MPa and a temperature of 55-65℃.
[0028] The specific steps of step D are as follows: Place the surface-modified carbon skeleton in a high-speed shear emulsifier, and add the silicon-based active unit raw material in three equal portions at a speed of 8000-12000 rpm, with an interval of 5 minutes between each addition. At the same time, atomized coal tar pitch is sprayed in during the shearing process, and the amount of sprayed accounts for 25-30% of the total mass of the silicon-based active unit to obtain a pre-composite.
[0029] In step F, the specific steps of element doping are as follows: in a mixed atmosphere of ammonia and nitrogen with a volume ratio of 1:10 to 1:12, the temperature is increased to 950-980°C at a rate of 5°C per minute and held for 60 minutes to obtain a nitrogen-doped silicon-carbon composite with a nitrogen content of 3.2-4.0 wt%.
[0030] In step G, the specific parameters for modifying the inner surface of the pores are as follows: the nitrogen-doped silicon-carbon composite is mixed with 0.3-0.4 mol / L ammonium citrate solution at a mass ratio of 1:10-12 and treated in a hydrothermal reactor at 200-210℃ for 8-10 hours.
[0031] Compared with the prior art, the advantages and beneficial effects of the present invention are as follows:
[0032] 1. This invention achieves effective buffering of volume expansion of silicon-based active units by designing a porous carbon framework with a specific hierarchical pore structure. Due to the pore size gradient distribution within the porous carbon framework, micropores provide high specific surface area to promote ion diffusion, mesopores primarily accommodate the radial deformation of silicon particles, and macropores form three-dimensional interconnected stress relief channels. This structural design confines the volume change of silicon-based active units during charging and discharging within local pores, avoiding damage to the overall electrode structure.
[0033] 2. In this invention, the carboxyl groups modified on the inner surface of the porous carbon framework form chemical bonds with the silicon suboxide layer of the silicon-based active unit, constituting an important interfacial stabilization mechanism. The oxygen atoms in the carboxyl groups form covalent bonds with the silicon atoms in the silicon suboxide layer, which significantly enhances the interfacial bonding strength between the silicon-based unit and the carbon framework. During repeated lithium-ion insertion and extraction, this strong interfacial interaction suppresses the tendency for separation between the silicon-based unit and the porous carbon framework, thereby maintaining the integrity of the ion and electron transport pathways.
[0034] 3. The conductive reinforced shell of this invention coats the outermost surface of the composite, establishing a continuous three-dimensional conductive network. This shell is composed of pyrolyzed carbon, with its thickness controlled at the nanometer level to ensure complete coverage without hindering ion migration. The conductive reinforced shell jointly encapsulates the outer surface of the porous carbon framework and the exposed silicon-based active units within the pores, achieving efficient charge transfer throughout the composite and significantly reducing interfacial contact resistance.
[0035] 4. This invention utilizes a mixed activation solution composed of potassium hydroxide and diammonium hydrogen phosphate to selectively corrode lignocellulose-derived carbon at a specific temperature, simultaneously constructing a hierarchical structure of micropores, mesopores, and macropores. This process avoids the generation of fluorine-containing toxic substances, and the activated waste liquid is nearly neutral and can be directly treated. Simultaneously, the presence of phosphate ions improves the thermal stability of the framework, reducing pore collapse in subsequent high-temperature steps.
[0036] 5. The elemental doping process of this invention is carried out in a mixed atmosphere of ammonia and nitrogen, and the uniform infiltration of nitrogen atoms into the carbon framework is achieved by controlling the temperature rise program. Nitrogen doping not only improves the intrinsic conductivity of the composite material, but the pyridine nitrogen structure formed also enhances the interaction force with lithium ions. Moreover, the nitrogen atoms doped inside the conductive reinforced shell enhance the chemical bonding strength between the carbon layer and the internal porous carbon framework, forming a conductive path that runs through both the inside and outside.
[0037] 6. The hydrothermal functionalization process of this invention enables the pyrolysis of ammonium citrate within the pores to generate free carboxyl groups. During this process, a pre-constructed silane coupling layer acts as a bridge, with its active silanol groups undergoing a condensation reaction with the carboxyl groups to achieve in-situ bonding. This directional modification method ensures that each carboxyl group points towards the center of the pore, maximizing the probability of contact with the silicon-based unit. The entire reaction is completed in a closed system, and unreacted organic components can be recycled.
[0038] 7. This invention achieves high dispersion of silicon particles by generating a strong shear force field and turbulence effect through high-speed shear emulsification. Simultaneously, atomized coal tar pitch is sprayed in the same state during high-speed shearing. The droplets immediately coat the surface of the silicon particles during collision, forming a physical isolation layer. This instantaneous barrier effect fundamentally prevents the re-agglomeration of silicon particles upon contact. The porous carbon skeleton is impregnated with a silane coupling agent solution of a specific concentration, constructing an interface layer containing organic functional groups on its surface. This weakens the agglomeration driving force caused by free particle migration at the source, ensuring that the silicon-based active units maintain their initial dispersed state throughout the electrochemical cycle, providing a core guarantee for a highly stable silicon-carbon anode. Detailed Implementation
[0039] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0040] In the specific embodiments of this application, the sources of various raw materials are briefly described as follows:
[0041] Potassium hydroxide: purchased from Sinopharm Chemical Reagent Co., Ltd., CAS No. 7646-40-5, analytical grade, content ≥85%;
[0042] Diammonium hydrogen phosphate: purchased from Xilong Scientific Co., Ltd., CAS No. 7803-57-8, analytical grade, purity ≥98.0%;
[0043] Deionized water: homemade, conductivity less than 0.1 μS / cm;
[0044] Silane coupling agent KH-550: purchased from Nanjing Shuguang Chemical Group Co., Ltd., CAS number 919-30-2, model SG-Si550;
[0045] Ethanol: Purchased from Sinopharm Chemical Reagent Co., Ltd., CAS No. 64-17-5, analytical grade, purity ≥99.5%;
[0046] Ammonium citrate: purchased from Aladdin Biochemical Technology Co., Ltd., CAS No. 3458-72-8, analytical grade, purity ≥99.0%;
[0047] Coal tar pitch: purchased from Hebei Deri New Material Technology Co., Ltd., CAS No. 8042-42-4, softening point 105-120℃;
[0048] Lignocellulose: Purchased from Shanghai Maclean Biochemical Technology Co., Ltd., model number W200733, purity ≥95%, particle size 100-200 mesh.
[0049] The technical solution of this application is as follows:
[0050] A porous carbon material for silicon-carbon anodes, the porous carbon material for silicon-carbon anodes having the following structure:
[0051] Porous carbon framework: It has a hierarchical pore structure, including micropores with a pore size of 0.5-2 nm, mesopores with a pore size of 10-30 nm, and macropores with a pore size of 100-300 nm.
[0052] Silicon-based active units: uniformly dispersed in the mesopores and macropores of the porous carbon framework, wherein the silicon-based active units are composed of a nano-silicon particle core and a silicon suboxide layer covering its surface;
[0053] Conductive reinforced shell: a vapor-phase pyrolysis carbon layer that completely covers the outer surface of the composite material consisting of a porous carbon framework and silicon-based active units.
[0054] The porous carbon framework has a porosity of 38-45%, of which micropores account for 40-60%, mesopores account for 25-40%, and the remainder is macropores.
[0055] The thickness of the conductive reinforced shell is 2-8 nanometers.
[0056] The silicon-based active unit accounts for 25-40% of the total mass of the porous carbon material used in the silicon-carbon anode. The average particle size of the nano-silicon particle core in the silicon-based active unit is 80-150 nanometers, and the thickness of the silicon suboxide layer is 5-15 nanometers with an oxygen-silicon atomic ratio of 0.8-1.2.
[0057] The inner surface of the hierarchical pore structure of the porous carbon skeleton is modified with carboxyl groups, which form chemical bonds with the silicon suboxide layer of the silicon-based active unit.
[0058] A method for preparing a porous carbon-based material for silicon-carbon anodes, the method comprising the following steps:
[0059] Step A: Preparation of porous carbon framework precursor: Lignocellulose is heated in an argon atmosphere tube furnace to obtain pre-carbonized products;
[0060] Step B: Graded pore-forming treatment: Immerse the pre-carbonized product in a mixed activator solution, control the solid-liquid mass ratio to 1:5 to 1:8, and stir continuously at 80-95℃ for 180 minutes to obtain a primary porous carbon skeleton.
[0061] Step C: Surface functionalization treatment: Immerse the primary porous carbon skeleton in a surface modifier, remove it after 30 minutes, and dry and cure it to obtain a surface-modified carbon skeleton with a silane coupling layer formed on its surface.
[0062] Step D: Silicon-based active unit composite: The surface-modified carbon skeleton is subjected to high-speed shear emulsification, while silicon-based active unit raw materials are added in batches, and atomized coal tar pitch is sprayed in to obtain a pre-composite.
[0063] Step E: Construction of conductive reinforced shell: The precomposite is transferred into a fluidized bed reactor and a mixed gas of acetylene and argon in a volume ratio of 1:4-5 is introduced. The mixture is then pyrolyzed and deposited at 650-750℃ for 45-60 minutes to form a carbon-coated silicon-carbon composite with a gas-phase pyrolyzed carbon layer on the surface.
[0064] Step F: Elemental doping treatment: Using carbon-coated silicon-carbon composite as raw material, elemental doping is performed in a mixed atmosphere to obtain nitrogen-doped silicon-carbon composite;
[0065] Step G: Channel Functionalization: The inner surface of the nitrogen-doped silicon-carbon composite is modified to modify the hierarchical pore structure with carboxyl groups, resulting in the finished porous carbon material for silicon-carbon anodes.
[0066] In step A, the specific parameters are as follows: 100-200 mesh lignocellulose is placed in an argon atmosphere tube furnace and heated to 450-550°C at a rate of 10°C per minute, and held for 60 minutes to obtain a pre-carbonized product.
[0067] In step B, the mixed activator solution comprises: 15-25 parts by mass of potassium hydroxide, 8-15 parts by mass of diammonium hydrogen phosphate, and 60-80 parts by mass of deionized water.
[0068] In step C, the surface modifier is an ethanol solution of silane coupling agent KH-550 with a mass percentage concentration of 2.5%-3.5%; the drying and curing are carried out under vacuum conditions of 0.02-0.04 MPa and a temperature of 55-65℃.
[0069] The specific steps of step D are as follows: Place the surface-modified carbon skeleton in a high-speed shear emulsifier, and add the silicon-based active unit raw material in three equal portions at a speed of 8000-12000 rpm, with an interval of 5 minutes between each addition. At the same time, atomized coal tar pitch is sprayed in during the shearing process, and the amount of sprayed accounts for 25-30% of the total mass of the silicon-based active unit to obtain a pre-composite.
[0070] In step F, the specific steps of element doping are as follows: in a mixed atmosphere of ammonia and nitrogen with a volume ratio of 1:10 to 1:12, the temperature is increased to 950-980°C at a rate of 5°C per minute and held for 60 minutes to obtain a nitrogen-doped silicon-carbon composite with a nitrogen content of 3.2-4.0 wt%.
[0071] In step G, the specific parameters for modifying the inner surface of the pores are as follows: the nitrogen-doped silicon-carbon composite is mixed with 0.3-0.4 mol / L ammonium citrate solution at a mass ratio of 1:10-12 and treated in a hydrothermal reactor at 200-210℃ for 8-10 hours.
[0072] The advantage of this application lies in its innovative integration of a triple mechanism: the hierarchical pores (micropores / mesopores / macropores) of the porous carbon framework disperse the expansion stress of silicon particles, reducing the risk of electrode deformation; the carboxyl groups on the inner wall of the pores form covalent bonds with the silicon suboxide layer of the silicon unit, strengthening the interfacial bonding strength and inhibiting the detachment of active materials; and the outermost gas-phase pyrolysis carbon layer constructs a global conductive network, ensuring efficient charge transport.
[0073] The technical solutions of the present invention are further illustrated below through examples and comparative examples, but the scope of protection of the present invention is not limited thereto.
[0074] Example 1
[0075] Step A: Take 100-mesh lignocellulose raw material and heat it to 550 degrees Celsius in an argon atmosphere tube furnace at a rate of 10 degrees Celsius per minute, and hold it at that temperature for 60 minutes to obtain the pre-carbonized product.
[0076] Step B: Take 15 grams of the product and immerse it in a mixed activator solution containing 15 parts by mass of potassium hydroxide, 10 parts by mass of diammonium hydrogen phosphate and 80 parts by mass of deionized water. The solid-liquid mass ratio is controlled at 1:8. Stir continuously at 95 degrees Celsius for 180 minutes to obtain a primary porous carbon framework.
[0077] Step C involves immersing the sample in a 3.5% (w / w) ethanol solution of silane coupling agent KH-550. After 30 minutes, the sample is removed and dried and cured under a vacuum pressure of 0.04 MPa and a temperature of 65 degrees Celsius to form a surface silane coupling layer.
[0078] Step D: Place 20 grams of the processed skeleton in a high-speed shear emulsifier and run it at 12,000 rpm. Add 40 parts by mass of silicon-based active unit raw material in three equal portions, with a 5-minute interval between each addition. Simultaneously spray in 30% of the total mass of silicon-based active units using atomized coal tar pitch to obtain a pre-composite. In this embodiment, the silicon-based active unit consists of a nano-silicon particle core and a silica sub-oxide layer coating its surface. In this embodiment, spherical nano-silicon particles are prepared by plasma vapor deposition. Then, the nano-silicon particles are placed in a fluidized bed reactor, and an oxygen / argon mixture is introduced. Heating and oxidation are performed to coat the nano-silicon particles with a silica sub-oxide layer, resulting in the silicon-based active unit. The specific preparation steps and parameters are known techniques and will not be described in detail here.
[0079] Step E: Transfer this pre-composite to a fluidized bed reactor, introduce a mixture of acetylene and argon in a volume ratio of 1:5, and pyrolyze and deposit it at 750 degrees Celsius for 45 minutes to form a gas-phase pyrolyzed carbon-coated composite.
[0080] Step F is then placed in a mixed atmosphere of ammonia and nitrogen in a volume ratio of 1:12, and heated to 980 degrees Celsius at a rate of 5 degrees Celsius per minute, and held at that temperature for 60 minutes to complete nitrogen doping.
[0081] Step G: Finally, the product is mixed with 0.3 mol / L ammonium citrate solution at a mass ratio of 1:12 and placed in a hydrothermal reactor at 200 degrees Celsius for 10 hours to obtain the final product.
[0082] Example 2
[0083] In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows:
[0084] Step A: Take 200-mesh lignocellulose raw material and pre-carbonize it in an argon atmosphere tube furnace to 450 degrees Celsius using the same heating program.
[0085] Step B: Take 20 grams of the product and mix it with a mixed activator solution containing 25 parts by mass of potassium hydroxide, 15 parts by mass of diammonium hydrogen phosphate and 70 parts by mass of deionized water. The solid-liquid mass ratio is set to 1:5. Stir at 80 degrees Celsius for 180 minutes.
[0086] Step C involves treatment with a 2.5% (w / w) silane coupling agent KH-550 ethanol solution followed by curing under a vacuum pressure of 0.02 MPa and a temperature of 55 degrees Celsius.
[0087] Step D: Place the modified skeleton in an emulsifier at 8000 rpm and add 25 parts by weight of silicon-based active unit raw material in three batches, while simultaneously spraying in 25% coal tar pitch.
[0088] Step E: Mix acetylene / argon in a fluidized bed at a ratio of 1:4.5 and deposit at 700 degrees Celsius for 60 minutes.
[0089] Step F involves heating the gas to 950 degrees Celsius in an atmosphere of ammonia / nitrogen = 1:111 and holding it at that temperature.
[0090] Step G involves reacting the nitrogen-doped complex with a 0.35 mol / L ammonium citrate solution at a ratio of 1:11 at 210°C for 9 hours using hydrothermal reaction.
[0091] Example 3
[0092] In this embodiment, the similarities to those in Embodiment 1 will not be repeated, and the differences are as follows:
[0093] Step A: Take 150-mesh lignocellulose raw material and heat it to 500 degrees Celsius in argon gas for pre-carbonization.
[0094] Step B: Mix 18g of the product with a mixed activator containing 20 parts by mass of potassium hydroxide, 12 parts by mass of diammonium hydrogen phosphate and 75 parts by mass of deionized water, with a solid-liquid ratio of 1:6, and stir at 88 degrees Celsius.
[0095] Step C involves modification with a 3.0% silane coupling agent KH-550 solution followed by drying under 0.03 MPa vacuum at 60 degrees Celsius.
[0096] Step D: Add 32 parts by mass of silicon-based active unit raw material at a speed of 10,000 revolutions per minute, and simultaneously spray in 28% coal tar pitch.
[0097] Step E: Deposition in a fluidized bed at 650 degrees Celsius for 52 minutes with acetylene / argon at a ratio of 1:4.
[0098] Step F involves heating the gas to 965 degrees Celsius using a 1:10 mixture of ammonia and nitrogen.
[0099] Step G is finally reacted with 0.4 mol / L ammonium citrate solution at a ratio of 1:10 at 205 degrees Celsius for 8 hours via hydrothermal reaction.
[0100] Comparative Example 1
[0101] In this comparative example, the similarities with Example 1 will not be repeated, and the differences are as follows:
[0102] The porous carbon framework contains only a single pore size (300-500 nanometer macropores).
[0103] Comparative Example 2
[0104] In this comparative example, the similarities with Example 2 will not be repeated, and the differences are as follows:
[0105] Cancel step C, surface functionalization, and step G, hydrothermal treatment process.
[0106] Comparative Example 3
[0107] In this comparative example, the similarities with Example 3 will not be repeated, and the differences are as follows:
[0108] Gas-phase pyrolysis carbon deposition was not performed in step E.
[0109] Comparative Example 4
[0110] In this comparative example, the similarities with Example 1 will not be repeated, and the differences are as follows:
[0111] The activator in step B contains only potassium hydroxide (to remove diammonium hydrogen phosphate).
[0112] Comparative Example 5
[0113] In this comparative example, the similarities with Example 1 will not be repeated, and the differences are as follows:
[0114] In step D, a sucrose solution is used instead of coal tar pitch.
[0115] Comparative Example 6
[0116] In this comparative example, the similarities with Example 1 will not be repeated, and the differences are as follows: However, the pyrolysis deposition time in step E is extended to 90 minutes, resulting in an increase in the thickness of the conductive reinforced shell to 15 nanometers.
[0117] Comparative Example 7
[0118] In this comparative example, the similarities with Example 2 will not be repeated, and the differences are as follows:
[0119] The activator in step B is changed to: 30 parts by mass of potassium hydroxide, 5 parts by mass of diammonium hydrogen phosphate, and 65 parts by mass of deionized water.
[0120] Comparative Example 8
[0121] In this comparative example, the similarities with Example 3 will not be repeated, and the differences are as follows:
[0122] Step F is changed to: In a pure ammonia atmosphere (without nitrogen dilution), the temperature is rapidly increased to 1000℃ at a rate of 20℃ / min and held for 60 minutes.
[0123] Comparative Example 9
[0124] In this comparative example, the similarities with Example 1 will not be repeated, and the differences are as follows:
[0125] Step C, surface functionalization (without silane coupling layer), is cancelled; only step G, hydrothermal treatment, is performed.
[0126] Performance Test Results and Analysis
[0127] Porous carbon-based materials for silicon-carbon anodes were prepared according to the parameters of the examples and comparative examples, respectively. The materials were tested, and the test results are shown in Table 1.
[0128] The pore structure characteristics, including average pore size, porosity, and pore size distribution at each level, were analyzed using gas adsorption (BET). The carboxyl bond density was quantitatively characterized using X-ray photoelectron spectroscopy (XPS) combined with chemical titration. The interfacial exfoliation force between the active unit and the carbon skeleton was measured using atomic force microscopy (AFM) nano-scraping technology. Capacity retention was determined by performing 100 charge-discharge cycles at 0.5C using a Blue Battery testing system. The thickness change of the electrode before and after cycling was measured using a micrometer to calculate the expansion rate. The thickness of the conductive reinforced shell was statistically measured using transmission electron microscopy (TEM) through local sampling. The powder conductivity was measured using a four-probe method to evaluate the conductivity performance.
[0129] As shown in Table 1, the three embodiments exhibit significant advantages in several key performance indicators. Regarding the pore structure, Examples 1-3 demonstrate an ideal hierarchical pore size distribution, with the average pore size maintained within the range of 28-32 nanometers. The ratio of micropores, mesopores, and macropores is approximately 5:3:2, and the porosity is between 40% and 43%. This structure facilitates electrolyte wetting and provides effective ion transport channels. Furthermore, the gradient pore structure progressively absorbs stress during silicon particle volume expansion, as evidenced by the low expansion rates—all below 20%.
[0130] In contrast, Comparative Example 1, employing a single-pore structure, while exhibiting similar porosity, lacked the synergistic buffering effect of micropores and mesopores, resulting in an expansion rate as high as 47.6% and a significantly reduced cycle capacity retention rate to 62.3%. This demonstrates that hierarchical pores are crucial for mitigating volume changes. Comparative Example 4, due to the use of only potassium hydroxide during the activation stage without the introduction of diammonium hydrogen phosphate as a synergistic pore-forming agent, suffered from excessive micropore development and insufficient proportion of mesopores and macropores, leading to a decrease in porosity to 36%. This resulted in limited ion transport and reduced stress buffering capacity, with both capacity retention and expansion rate being inferior to the examples.
[0131] The interfacial bonding strength of this invention is reflected by both carboxyl bond density and peel force. In the examples, the carboxyl bond density is between 0.38 and 0.45 mmol / g, and the corresponding peel force reaches more than 126 nN, indicating that a strong covalent bond interface was successfully constructed between the inner surface of the carbon skeleton and the silicon suboxide layer of the silicon-based unit through surface silane coupling pretreatment and subsequent hydrothermal carboxylation modification.
[0132] Comparative Example 2, which omitted surface functionalization and hydrothermal treatment, experienced a sharp decrease in carboxyl bond density to 0.05 mmol / g and a peel strength of only 58 nN. The weak interfacial bonding led to easy detachment of active material after cycling, resulting in a significant reduction in capacity retention. Comparative Example 9, which only underwent hydrothermal treatment without the silane coupling step, had a bond density similar to the examples, but a significantly lower peel strength. This indicates that the silane coupling agent plays a crucial bridging role in creating bonding sites on the carbon surface and enhancing interfacial compatibility during pretreatment. While this step can introduce carboxyl groups, the bonding strength is insufficient.
[0133] Electrical conductivity is closely related to the properties of the outer shell. In the embodiments of this application, the thickness of the outer vapor-phase pyrolysis carbon layer is controlled within the range of 2 to 8 nanometers, and with nitrogen doping treatment, the powder conductivity is higher than 7.9 S / m.
[0134] Table 1 Analysis of Test Results
[0135]
[0136] Comparative Example 3, lacking vapor-phase pyrolysis carbon deposition, lacked a conductive outer shell. Despite good pore structure and interfacial bonding, its overall electron transport capability was severely insufficient, with a conductivity of only 2.1 S / m, directly resulting in low capacity retention. Comparative Example 6, due to excessive deposition time, resulted in an excessively thickened carbon layer of 14.2 nm. Although the interfacial bonding was good, the excessively thick inactive carbon layer increased ion transport resistance, leading to decreased conductivity and reduced capacity retention. Comparative Example 8, using a pure ammonia atmosphere without nitrogen dilution and rapid high-temperature doping, resulted in surface nitrogen species existing in a non-conductive form and increased disorder in the carbon layer structure. Although the nitrogen content may not be low, the conductivity decreased significantly, indicating that a mild nitrogen doping process is crucial for the formation of conductive nitrogen species.
[0137] Using coal tar pitch as a dispersant and binder in step D helps to form a uniform pre-composite during the composite process, which also plays a positive role in the subsequent formation of a complete conductive shell. Comparative Example 5, which used sucrose solution, resulted in a less dense carbonaceous structure after pyrolysis, insufficient continuity of the conductive network, and a decrease in conductivity to 5.8 S / m, indicating that the choice of precursor affects the quality of the final conductive structure.
[0138] In summary, the test results fully verify that the samples of the embodiments of the present invention achieve a good balance in cycle stability, volume expansion control and conductivity, which is significantly better than the comparative samples with various single mechanism deficiencies or process deviations, demonstrating their application potential in high-performance silicon-carbon anodes.
[0139] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A porous carbon material for silicon-carbon anodes, characterized in that, The porous carbon material used in this silicon-carbon anode has the following structure: Porous carbon framework: It has a hierarchical pore structure, including micropores with a pore size of 0.5-2 nm, mesopores with a pore size of 10-30 nm, and macropores with a pore size of 100-300 nm. Silicon-based active units: uniformly dispersed in the mesopores and macropores of the porous carbon framework, wherein the silicon-based active units are composed of a nano-silicon particle core and a silicon suboxide layer covering its surface; Conductive reinforced shell: a vapor-phase pyrolysis carbon layer that completely covers the outer surface of the composite material consisting of a porous carbon framework and silicon-based active units; The porous carbon framework has a porosity of 38-45%, of which micropores account for 40-60%, mesopores account for 25-40%, and the remainder is the proportion of macropores. The inner surface of the hierarchical pore structure of the porous carbon skeleton is modified with carboxyl groups, which form chemical bonds with the silicon suboxide layer of the silicon-based active unit.
2. The porous carbon material for silicon-carbon anodes according to claim 1, characterized in that, The thickness of the conductive reinforced shell is 2-8 nanometers.
3. The porous carbon material for silicon-carbon anodes according to claim 1, characterized in that, The silicon-based active unit accounts for 25-40% of the total mass of the porous carbon material used in the silicon-carbon anode. The average particle size of the nano-silicon particle core in the silicon-based active unit is 80-150 nanometers, and the thickness of the silicon suboxide layer is 5-15 nanometers with an oxygen-silicon atomic ratio of 0.8-1.
2.
4. A method for preparing a porous carbon material for a silicon-carbon anode as described in any one of claims 1-3, characterized in that, The preparation method includes the following steps: Step A: Preparation of porous carbon framework precursor: Lignocellulose is heated in an argon atmosphere tube furnace to obtain pre-carbonized products; Step B: Graded pore-forming treatment: Immerse the pre-carbonized product in a mixed activator solution, control the solid-liquid mass ratio to 1:5 to 1:8, and stir continuously at 80-95℃ for 180 minutes to obtain a primary porous carbon skeleton. Step C: Surface functionalization treatment: Immerse the primary porous carbon skeleton in a surface modifier, remove it after 30 minutes, and dry and cure it to obtain a surface-modified carbon skeleton with a silane coupling layer formed on its surface. Step D: Silicon-based active unit composite: The surface-modified carbon skeleton is subjected to high-speed shear emulsification, while silicon-based active unit raw materials are added in batches, and atomized coal tar pitch is sprayed in to obtain a pre-composite. Step E: Construction of conductive reinforced shell: The precomposite is transferred into a fluidized bed reactor and a mixed gas of acetylene and argon in a volume ratio of 1:4-5 is introduced. The mixture is then pyrolyzed and deposited at 650-750℃ for 45-60 minutes to form a carbon-coated silicon-carbon composite with a gas-phase pyrolyzed carbon layer on the surface. Step F: Elemental doping treatment: Using carbon-coated silicon-carbon composite as raw material, elemental doping is performed in a mixed atmosphere to obtain nitrogen-doped silicon-carbon composite; Step G: Channel Functionalization: The inner surface of the nitrogen-doped silicon-carbon composite is modified to modify the hierarchical pore structure with carboxyl groups, resulting in the finished porous carbon material for silicon-carbon anodes.
5. The method for preparing porous carbon material for silicon-carbon anodes according to claim 4, characterized in that, In step A, the specific parameters are as follows: 100-200 mesh lignocellulose is placed in an argon atmosphere tube furnace and heated to 450-550°C at a rate of 10°C per minute, and held for 60 minutes to obtain a pre-carbonized product. In step B, the mixed activator solution comprises: 15-25 parts by mass of potassium hydroxide, 8-15 parts by mass of diammonium hydrogen phosphate, and 60-80 parts by mass of deionized water.
6. The method for preparing porous carbon material for silicon-carbon anodes according to claim 4, characterized in that, In step C, the surface modifier is an ethanol solution of silane coupling agent KH-550 with a mass percentage concentration of 2.5%-3.5%; the drying and curing are carried out under vacuum conditions of 0.02-0.04 MPa and a temperature of 55-65℃.
7. The method for preparing a porous carbon material for a silicon-carbon anode according to claim 4, characterized in that, The specific steps of step D are as follows: Place the surface-modified carbon skeleton in a high-speed shear emulsifier, and add the silicon-based active unit raw material in three equal portions at a speed of 8000-12000 rpm, with an interval of 5 minutes between each addition. At the same time, atomized coal tar pitch is sprayed in during the shearing process, and the amount of sprayed accounts for 25-30% of the total mass of the silicon-based active unit to obtain a pre-composite.
8. The method for preparing porous carbon material for silicon-carbon anodes according to claim 4, characterized in that, In step F, the specific steps of element doping are as follows: in a mixed atmosphere of ammonia and nitrogen with a volume ratio of 1:10 to 1:12, the temperature is increased to 950-980℃ at a rate of 5℃ per minute and held for 60 minutes to obtain a nitrogen-doped silicon-carbon composite with a nitrogen content of 3.2-4.0 wt%; in step G, the specific parameters for modifying the inner surface of the pores are as follows: the nitrogen-doped silicon-carbon composite is mixed with a 0.3-0.4 mol / L ammonium citrate solution at a mass ratio of 1:10-12 and treated in a hydrothermal reactor at 200-210℃ for 8-10 hours.
Citation Information
Patent Citations
Si / SiOx / C ternary composite material and preparation method thereof
CN115602809A
Nano silicon-carbon composite material as well as preparation method and application thereof
CN118173733A